A202 ROLE OF EXTRACELLULAR VESICLES IN GIARDIA-MICROBIOTA INTERACTIONS. (4th March 2021) - Siddiq, A; Allain, T; Dong, G; Olivier, M; Buret, A
Abstract: Background: Extracellular vesicles (EVs) have emerged as important mediators of host-parasite interactions. Studies in various parasites have shown that EVs have important roles in pathogenesis. The protozoan parasite Giardia duodenalis, which causes diarrheal disease, produces EVs in response to changes in the environment. However, their exact role in the pathogenesis of giardiasis remains unclear. In this study, we investigate the effects of Giardia EVs on the gut commensal bacteria. EVs mediated disruption of the microbiota represents a novel mechanism that has not been investigated before. Aims: We hypothesize that Giardia EVs contain virulence factors that will modify the growth and behavior of commensal bacteria. Based on our hypothesis, the study has three aims: 1. Quantify and characterize the EVs produced by Giardia under varying conditions. 2. Examine the effects of Giardia EVs on commensal bacteria. 3. Identify proteins and virulence factors in Giardia EVs using proteomics. Methods: G. duodenalis (isolate NF) was exposed to bile or left untreated and the EVs were isolated using Exo-Easy Maxi Kit (Qiagen). The isolated EVs were characterized using Nanosight track analysis (NTA) and transmission electron microscopy. To examine the effects of EVs on bacteria, we used a lab strain E.coli HB101 and human isolate E. cloacae. The bacteria were incubated with Giardia EVs and their growth rate was monitored using a bacterial kinetics assay. The swimming motility of bacteria exposed to Giardia EVs was assessed on a 0.3% agar. Additionally, the ability of the EVs treated bacteria to adhere to epithelial cells was also examined. Proteomic analysis of EVs was conducted using liquid chromatography with tandem mass spectrometry. Results: Results indicate that bile treated Giardia trophozoites produce more EVs as compared to untreated trophozoites. Giardia EVs exerted bacteriostatic effects on E.coli HB101 and E. cloacae . Additionally, Giardia EVs significantly increased the swimming motility of both E.coli HB101 and E. cloacae as well as their adhesion to the intestinal epithelial cells. Finally, proteomic analysis of EVs revealed the presence of well-characterized Giardia virulence factors such as cysteine proteases, tenascins, variant surface proteins as well as metabolic enzymes such as arginine deaminase and ornithine carbamoyltransferase. Conclusions: Our research highlights a novel mechanism of Giardia's interaction with commensal bacteria. Our results indicate that Giardia can release EVs in response to changes in the environment. These EVs also contain virulence factors that can modify the growth and behavior of commensal bacteria. These effects may have significant implications in disease pathophysiology. The results of the study can also be applied to other parasitic diseases where the production of EVs has been shown to play a role in the pathogenesis process. Funding Agencies: NSERC